(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
In this article, we have revealed the formation and development of writing skills, which is one of the most pressing problems today, and the system of exercises as an example.